Principais complicações perinatais da obesidade e do sobrepeso pré-gestacionais - Cidade, Denise Gomes; Margotto, Paulo Roberto; Peraçoli, José Carlos [UNESP] (My University, 2011)
Objetive: The goal of this review is to discuss the evidence regarding the impact of pre-pregnancy overweight and obesity on perinatal outcomes. Data Collection Method: We conducted a search for articles in the Medline, PubMed and Scielo databases covering the past 5 years, and reviewed the bibliographical references contained in the articles selected. Articles were selected by subjective evaluation in terms of methodology, sample size and year of publication. Summary of evidence: We found strong evidence linking excess weight before pregnancy with the development of birth defects, fetal and neonatal deaths and macrosomia,. Conclusions: Excess weight in the pre-pregnancy is an important risk factor for the health of the fetus, whose importance increases because it is a modifiable risk factor.

Objetivo: O objetivo desta revisão é discutir as evidências atuais acerca do impacto do sobrepeso e da obesidade pré-gestacionais nos resultados perinatais. Método de coleta dos dados: Os artigos utilizados foram obtidos por meio de pesquisa nos bancos de dados MedLine/PubMed e SciELO abrangendo os últimos 5 anos e por meio da revisão das referências bibliográficas dos artigos selecionados. Os artigos encontrados foram selecionados por avaliação subjetiva, considerando metodologia, tamanho da amostra, coerência nas conclusões e o ano de publicação. Síntese da evidência: Fortes evidências associam o excesso de peso no período pré-gestacional e no início da gestação a malformações congê- nitas, morte fetal e neonatal e macrossomia. Conclusões: O excesso de peso no período pré-gestacional é um importante fator de risco à saúde do concepto, cuja importância aumenta por se tratar de fator de risco modificável.
Major perinatal complications of pre-pregnancy obesity and overweight
Keywords: Obesity; Pregnancy outcomes; Perinatal morbidity; Macrosomia; Fetal death; Obesidade; Resultados da gravidez; Morbidade perinatal; Macrossomia; Morte fetal